ANALISIS STRATEGI BERSAING DALAM PENINGKATAN JUMLAH KONSUMEN PADA PERUSAHAAN JASA MENGEMUDI BARUNA NGANJUK - Sundari , Mita; Respatiningtias, Dyah Suswanti (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study is to find out the competitive strategies applied to the Baruna Nganjuk Driving Course and the competitive strategies applied to the Baruna Nganjuk Driving Course in increasing the number of consumers. The research method used by researchers is descriptive with a qualitative approach. The data collection techniques in question are in the form of questionnaires, interviews, observation, and documentation. Data analysis techniques are processed by analyzing the data theoretically so that IFAS (Internal Strategic Factor Analysis Summary) and EFAS (External Strategic Factor Analysis Summary) can be found using the analysis SWOT method in Baruna Nganjuk's driving course. The results of this study prove that the data regarding the position of the company using SWOT analysis shows that the Baruna Nganjuk driving course service business is in a business growth phase. With an internal factor value of 3.02 and an external factor value of 3.39. A suitable marketing strategy applied to the Baruna Nganjuk driving course services in increasing the number of consumers is to use SO (Strength Opportunities) strategy. The SO strategy is carried out by harnessing the company's strengths by capturing high market opportunities.